ANALISIS PENENTUAN HARGA POKOK PRODUKSI (HPP) PADA USAHA KECIL MENENGAH (UKM) NARASA ABADI PALU - Nadhira Afdalia; Chalarce Totanan; Yuldi Mile (SIMAK, 2020)
Narasa Abadi Small and Medium Enterprises(SMEs) is one of the developing SMEs in the city of Palu. SMEs Narasa abadi producing a variety of snack. The calculation of the Cost Of Goods Manufactured carried out by SMEs is generally still very simple. This study aims to analyze the Cost Of Goods Manufactured in Narasa Abadi because of the importance of determining the Cost Of Goods Manufactured as information for determining selling prices. Based on the results of the analysis of Narasa Abadi still calculating the Cost Of Goods Manufactured in a simple way, information on Cost Of Goods Manufactured used by the Narasa Abadi is not appropriate so that it will affect the selling price and other important decisions